Neuroimaging - Structure, Function and Mind 2019
DOI: 10.5772/intechopen.80888
|View full text |Cite
|
Sign up to set email alerts
|

Vector-Based Approach for the Detection of Initial Dips Using Functional Near-Infrared Spectroscopy

Abstract: Functional near-infrared spectroscopy (fNIRS) is a non-invasive method for the detection of local brain activity using changes in the local levels of oxyhemoglobin (oxyHb) and deoxyhemoglobin (deoxyHb). Simultaneous measurement of the levels of oxyHb and deoxyHb is an advantage of fNIRS over other modalities. This review provides a historical description of the physiological problems involved in the accurate identification of local brain activity using fNIRS. The need for improved spatial and temporal identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 100 publications
1
15
0
Order By: Relevance
“…Magnitude and angle, calculated using HbO and HbR, are used to construct a two-dimensional vector plane [33]. This plane is divided into eight phases for the classification of hemodynamic response [34]. A threshold circle is plotted on the vector plane to detect brain activity [35].…”
Section: Literature Review and Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Magnitude and angle, calculated using HbO and HbR, are used to construct a two-dimensional vector plane [33]. This plane is divided into eight phases for the classification of hemodynamic response [34]. A threshold circle is plotted on the vector plane to detect brain activity [35].…”
Section: Literature Review and Related Workmentioning
confidence: 99%
“…If the trajectory of HbO and HbR crosses this threshold circle, this indicates activity. Magnitude values less than this threshold circle are considered as resting-state [34,35,38]. Initial dip and hemodynamic response can be detected in these eight phases.…”
Section: Vector Phase Analysismentioning
confidence: 99%
“…OxyHb increased and deoxyHb fell slightly in the sensory-motor cortex and the pre-SMA (Hatakenaka et al, 2007 ). Several reports have shown that oxyHb analysis alone cannot accurately detect the localization of neuroactivation (Cyranoski, 2011 ; Takahashi et al, 2011 ) and that functional images of increasing oxyHb may differ from the actual distribution of oxygen consumption (Kato, 2018 , 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the oxygen consumption and supply triggered by neuroactivation cannot be evaluated simultaneously based on deoxyHb alone. In terms of technological advances, earlier NIRS was used as a cerebral oxygen monitor that could be measured over the scalp, and it was not until July 1991 that it was first successfully demonstrated that fNIRS could detect regional brain function (Kato, 2018 ). In addition, there was a lack of theory to quantitatively integrate neural activation from multiple sites (channels) and indices (Kato et al, 1993 ; Ferrari and Quaresima, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation